Adjustment to Pubertal Changes among Adolescent Girls - Ajanta Maharjan Singh; Manisha Koirala (Janaki Medical College Journal of Medical Science, 2023)
Background and Objectives: Adolescence is the transitional stage of life from childhood to adulthood characterized by puberty. Dramatic physical, physiological, hormonal, and emotional changes occur, which are exciting as well as frightening at the same time. The objective of this study was to find out the adjustment of adolescent girls towards pubertal changes. Materials and Methods: A descriptive cross-sectional study was conducted to find out the adjustment toward pubertal changes among adolescent girls studying in Grades 8, 9, and 10. A proportionate stratified random sampling technique was used to collect the samples, and a self-administered structured questionnaire was used. Descriptive statistics was used to analyze the data. Results: All the respondents had experienced a rapid increase in height, weight, and development of breast bud, almost all (92.8%) had experienced pubic hair growth, the majority (85.6%) had experienced axillary hair growth, and three-fourths (76%) had experienced pimples on the face. Most (88.8%) of the respondents had received pre-information about pubertal changes. During menarche, more than two-thirds (68.0%) were restricted from worshipping, 20.8% were restricted from seeing or talking to male family members, 17.6% were restricted from cooking and doing household work, and 16.0% were kept in a separate room or neighbor’s house. Nearly three-fourths (74.4%) of the respondents used sanitary pads during their menarche. Similarly, more than three-fourths (77.6%) of the respondents experienced problems during menarche, and the majority (80.4%) had lower abdominal pain. Regarding emotional changes, nearly two-thirds (63.2%) had frequent mood swings, and nearly half (45.6%) shared their feelings with family members and friends. Conclusion: Almost all the respondents have adjusted well to the pubertal changes, but restriction during menarche is still prevalent which needs to be addressed for respectful care during menstruation.